Multimodal Pain Management and Postoperative Outcomes in Lumbar Spine Fusion Surgery: A Population-based Cohort Study. Issue 9 (1st May 2020) - Cozowicz, Crispiana; Bekeris, Janis; Poeran, Jashvant; Zubizarreta, Nicole; Schwenk, Eric; Girardi, Federico; Memtsoudis, Stavros G.
Abstract : Study Design: Retrospective population-based cohort analysis. Objective: Given the lack of large-scale data on the use and efficacy of multimodal analgesia in spine fusion surgery, we conducted a population-based analysis utilizing the nationwide claims-based Premier Healthcare database. Summary of Background Data: Multimodal analgesia, combining different pain signaling pathways to achieve additive and synergistic effects, is increasingly emerging as the standard of care. Methods: Cases of posterior lumbar fusion surgery were extracted (2006–2016). Opioid-only analgesia was compared to multimodal analgesia, that is, systemic opioid analgesia + either acetaminophen, steroids, gabapentinoids, ketamine, nonsteroidal anti-inflammatory drugs (NSAIDs), cyclooxygenase-2 (COX-2) inhibitors, or neuraxial anesthesia (categorized into 1, 2, or >2 additional analgesic modes). Mixed-effects models measured associations between multimodal analgesia categories and outcomes, including opioid prescription dose, cost/length of hospitalization, and opioid-related complications. Odds ratios (ORs, or % change) and 95% confidence intervals (CIs) are reported. Results: Among 265, 538 patients the incidence of multimodal analgesia was 61.1% (162, 156); multimodal pain management—specifically when adding NSAIDs/COX-2 inhibitors to opioids—was associated with reduced opioid prescription (−13.3% CI −16.7 to −9.7%), cost (−2.9% CI −3.9 to −1.8%) and length of hospitalization (−7.3% CI −8.5 to −6.1%). Multimodal analgesia in general was associated with stepwise decreased odds for gastrointestinal complications (OR 0.95, 95% CI 0.88–1.04; OR 0.84, CI 0.75–0.95; OR 0.78, 95% CI 0.64–0.96), whereas odds were increased for postoperative delirium (OR 1.14, 95% CI 1.00–1.32; OR 1.33, 95% CI 1.11–1.59; OR 1.31, 95% CI 0.99–1.74), and counterintuitively- naloxone administration (OR 1.25, 95% CI 1.13–1.38; OR 1.56, 95% CI 1.37–1.77; OR 1.84, 95% CI 1.52–2.23) with increasing analgesic modes used: one, two, or more additional analgesic modes, respectively. Post-hoc analysis revealed that specifically gabapentinoid use increased odds of naloxone requirement by about 50%, regardless of concurrent opioid dose ( P  < 0.001). Conclusion: Although multimodal analgesia was not consistently implemented in spine fusion surgery, particularly NSAIDs and COX-2 inhibitors demonstrated opioid sparing effects. Moreover, results suggest a synergistic interaction between gabapentinoids and opioids, the former potentiating opioid effects resulting in greater naloxone requirement. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textThe implementation of multimodal analgesia appears to be relatively low in spine fusion surgery, despite the severity of pain. Moreover, while multimodal pain management was associated with opioid sparing—specifically when nonsteroidal anti-inflammatory drugs/cyclooxygenase-2 inhibitors were utilized—results suggest a synergistic interaction between the concurrent use of gabapentinoids and opioids, potentially driving increased naloxone requirement.